Upaya Meningkatkan Motivasi Belajar Siswa melalui Model Pembelajaran Kooperatif - Yella Josa Aprista; Meliyar Susanti (Kampus Akademik Publiser, 2024)
This research aims to increase students' learning motivation through cooperative learning model. Learning motivation is one of the key factors in the success of the learning process. The low motivation of students is often an obstacle in achieving optimal learning outcomes. This research aims to examine the effectiveness of cooperative learning model in increasing students' learning motivation. The cooperative learning model encourages students to work together in small groups, help each other understand the material, and actively participate in the learning process. Through positive social interaction and shared responsibility, students become more motivated to be actively involved in learning activities. The results of the study show that the application of cooperative learning can increase students' confidence, responsibility, and interest in the subject matter. This research used the Classroom Action Research (PTK) method using a cyclical system consisting of planning, implementation, observation, analysis and reflection. The research was conducted in three cycles with stages of planning, action implementation, observation, and reflection. The research subjects were 15 fifth grade students of SDN 29 Sungai Nipah. Data were collected through learning outcome tests and observation of student activities during the learning process. In cycle I, only 60% of students reached the Minimum Completion Criteria (KKM). After the improvement of learning in cycle II, the completeness increased to 73%, and in cycle III all students (100%) reached the KKM. This increase shows that the cooperative learning model is able to increase student motivation and activeness.